Information searching: The impact of user knowledge on user search behavior - Mat Yamin, Fadhilah; Ramayah, T.; Wan Ishak, Wan Hussain (World Scientific Publishing Co., 2013)
The utilisation of Information and Communication Technology (ICT) and networked information infrastructure in a wide range of businesses and activities has increased the need for fast and reliable information.The information is vital for innovation, competition, and decision making. To date information gathering is no longer absolute from the library, nonetheless the information can be retrieved from all around the world through Internet technology. However, information searching is a tedious process.Knowledge has been identified in this paper as the important factor that affects the searching behaviour.User knowledge is measured by topic and search system understanding while searching behaviour is measured by the breadth and depth of the search query.Both knowledge reflects the true understanding of what and how to search.The breadth and depth of search query show the users' effort in completing the search.In this paper, the impact of user knowledge on search behaviour is accessed on the education domain.Final year undergraduate students were identified as the population that "grown with the web" as they are actively using the Internet to fulfil their study requirement. The findings show that user knowledge does have an impact on the search behaviour.